Lithic Techno-Typology and Chronometry in the Late Mesolithic of the Sado Valley: the Case of Amoreiras Shell Midden (Alcácer do Sal, Portugal) - Nukushina, Diana (2014)
Amoreiras, a shell midden in the Sado valley (Southern Portugal), was during years considered one of the most recent sites of the Sado Mesolithic complex, and a place of interactions between the last hunter-gatherers and the Neolithic groups. Nevertheless, the data about the lithic industry was poorly known. The absolute chronology and the complexity of the stratigraphy were not analyzed in detail. In this paper, we present the results from a techno-typological analysis of a set of lithic materials recovered from the first excavations in Amoreiras during the 1950’s and 1960’s.